2023
DOI: 10.3390/vision7010023
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health State of Canadian Ophthalmologists during the COVID-19 Pandemic: A Survey-Based Study and Review

Abstract: The coronavirus disease 2019 (COVID-19) pandemic disrupted the practice of medicine, causing stress and uncertainty among ophthalmologists. This cross-sectional, survey-based study of Canadian Ophthalmological Society members (n = 1152) aims to report on Canadian ophthalmologists’ mental health during the COVID-19 pandemic. Four questionnaires were administered between December 2020 and May 2021: the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), the 7-item Insomnia Severity In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Similarly, most of the studies reported a significant increase in anxiety and stress among ophthalmologists during this pandemic. [ 7 8 ]…”
mentioning
confidence: 99%
“…Similarly, most of the studies reported a significant increase in anxiety and stress among ophthalmologists during this pandemic. [ 7 8 ]…”
mentioning
confidence: 99%